Regulatory sequences in the transcription of Neurospora crassa genes: CAAT box, TATA box, Introns, Poly(A) tail formation sequences - J. J. P. Bruchez; J. Eberle; V. E. A. Russo (Fungal Genetics Reports, 1993)
Minireview. Regulatory sequences in the transcription of Neurospora crassa genes: CAAT box, TATA box, Introns, Poly(A) tail formation sequences.